Implementation of a Camera System for the Application of Artificial Intelligence in Monitoring the Cold Atmospheric Plasma Spray Process - Ockel, Manuela; Meier, Sven; Stelter, Oliver; Thielen, Nils; Bründl, Patrick; Franke, Jörg (2024 32nd Mediterranean Conference on Control and Automation (MED), 2024)
Monitoring of the complex cold atmospheric plasma spraying process currently relies on technologically advanced systems, that often measure only a single parameter. This research introduces a more integrated approach, that uses a comprehensive set of parameters, consolidated in the characteristics of the plasma flame, is used to accurately classify particle temperature and coating materials. A simple optical camera system and image analysis based on a transfer learning model predicts with an 85% success rate. This approach simplifies and complements the monitoring process. Accuracy could be increased by using additional machine data already recorded, which could allow a complete replacement of additional the plasma flame monitoring.<br
Keywords: Temperature measurement; Temperature sensors; Temperature; Atmospheric measurements; Transfer learning; Process control; Fires; Cold Atmospheric Plasma Spray; Artificial Intelligence; Optical Process Monitoring; Electronics Production